2014
DOI: 10.1016/s2214-109x(14)70307-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a rural sanitation programme on diarrhoea, soil-transmitted helminth infection, and child malnutrition in Odisha, India: a cluster-randomised trial

Abstract: Bill & Melinda Gates Foundation, International Initiative for Impact Evaluation (3ie), and Department for International Development-backed SHARE Research Consortium at the London School of Hygiene & Tropical Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
482
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 458 publications
(507 citation statements)
references
References 31 publications
19
482
1
5
Order By: Relevance
“…An even stronger spillover effect is expected with respect to the coverage of proper sanitation in the community (Alderman et al, 2003). Although an improved toilet increases the hygiene level of the owner, it cannot fully eliminate faecal contamination from the neighbourhood if other households lack such a facility (Andres et al, 2014;Clasen et al, 2014). Indirect effects at the community level might also be important.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…An even stronger spillover effect is expected with respect to the coverage of proper sanitation in the community (Alderman et al, 2003). Although an improved toilet increases the hygiene level of the owner, it cannot fully eliminate faecal contamination from the neighbourhood if other households lack such a facility (Andres et al, 2014;Clasen et al, 2014). Indirect effects at the community level might also be important.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…But they have scope for further improvement (Hutchinson, 2006). In contrast, the sanitation program conducted in Odisha, India to prevent diarrhea, soil-transmitted helminth infection, and child malnutrition, for instance showed that though the quantitative coverage in constructing toilets were fulfilled, but the real success in terms of uptake could not be assumed (Clasen et al, 2014) . Other studies have also shown that mass media campaigns have been successful in bringing about positive changes or prevent negative changes in health-related behaviours across large populations (Wakefield, 2010).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Public health campaigns targeted to the rural population to improve their preventive and curative health practices are common places in developing countries (Clasen et al, 2014;Naugle & Hornik, 2014). These interventions have their respective costs and consequences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, the health benefits of sanitation, that is the separation and containment of human excreta, are entirely dependent on achieving a high, if not complete, level of coverage and use. Faeces contain a variety of disease-causing pathogens that are easily transmitted by feet, fingers, flies or fluids; even small amounts of faecal material in the environment can infect any number of people who themselves, use, or don't use a toilet, weakening or removing the effect of sanitation for the few who use it [17].…”
Section: Introductionmentioning
confidence: 99%